Antibacterial Activity of Various Solvent Extracts of the Indian Herbal Plant Acalypha indica against Human Pathogens Causing Nosocomial Infection - Murugan, T (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTNosocomial infections occur worldwide, both in the developed and developing world. They are a significant burden to patients and public health. They are a major cause of death and increased morbidity in hospitalized patients. They may cause increased functional disability and emotional stress and may lead to conditions that reduce quality of life. In this present study, the herbal plant Acalypha indica was tested for its antibacterial activity against Nosocomial infection causing bacteria. The Acalypha indica was shade dried and the antimicrobial principles were extracted with Methanol, Acetone, Chloroform, Petroleum Ether and Hexane. The antibacterial activity of Acalypha indica was determined by Agar Well Diffusion Method. It was found that 50mg/ml of methanolic extract of the plant able to inhibit the growth of nosocomial infection causing bacteria when compared to other solvent extracts. From this it was concluded that the solvent methanol able to leach out antimicrobial principle very effectively from the plant than the other solvents. The phytochemicals present in the Acalypha indica was tested and it conferred that the possible antibacterial principle resided in tannins and alkaloids.